Reavaliação do ciclo do epitélio seminífero no homem - Fabíola Nihi (2017)
Study question: Can all types of testicular germ cells be accurately identified by microscopy techniques and unambiguously distributed in stages of the human seminiferous epithelium cycle (SEC)? Summary answer: By using a high-resolution light microscopy (HRLM) method, which allows a better visualization of cell morphological features, we identified all testicular germ cells in the seminiferous epithelium and precisely grouped them into six well-delimitated SEC stages, thus providing a reliable reference source for staging in man. What is already known: Morphological characterization of germ cells in human has been done decades ago with the use of conventional histological methods (formaldehyde-based fixative -Zenker-formal- and paraffin embedding). These early studies proposed a classification of the SEC in six stages. However, the use of stages of human SEC as baseline for morphofunctional evaluations of testicular parenchyma has not been used because of the incomplete morphological identification of germ cells that lead to the difficulties to define the boundaries between stages and consequently divergent frequency data among researchers. Study design, size, duration: Testicular tissue from adult and elderly donors with normal spermatogenesis according to Levin’s, Johnsen’s and Bergmann’s scores were used to evaluate germ cell morphology and validate their distribution and frequency in stages along the human SEC. Participants/materials, setting, methods: Testicular tissue from patients diagnosed with congenital bilateral agenesis of vas deferens (n= 3 adults) or prostate cancer (n= 3 elderly) were fixed in gluraldehyde and embedded in araldite epoxy resin. Morphological analyses were performed by both light and transmission electron microscopy. Main results and the role of chance: HRLM method enabled a reliable morphological identification of all germ cells (spermatogonia, spermatocytes and spermatids) based on high-resolution aspects of euchromatin, heterochromatin and nucleolus. Moreover, acrosomal development of spermatids was clearly revealed. Altogether, our data redefined the limits of each stage leading to a more reliable determination of the SEC in man. Limitations, reasons for caution: Occasionally, germ cells can be absent in some tubular sections. In this situation, it has to be taken into account the germ cell association proposed in the present study to classify the stages. Wider implications of the findings: Our findings provide details of the germ cell composition of each stage of the human SEC. The different types of spermatids that make the composition of the cellular associations redefined the relative frequency data of the six SEC stages. The new descriptions by the HRLM will serve as a valuable tool for scientific studies on human spermatogenesis and may help to better understand testicular diseases and infertility conditions that remain unsolved.